Yb(OTf)3 catalyzed [3 + 2] annulations of D–A cyclopropanes with β-oxodithioesters: a regioselective synthesis of tetrahydrothiophenes1. Issue 59 (28th June 2015) - Wang, Shu-Wen; Guo, Wei-Si; Wen, Li-Rong; Li, Ming
<x xml:space="preserve">Abstract</x> An efficient approach to synthesis tetrahydrothiophenes was developed through the reaction of β-oxodithioesters and D–A cyclopropanes catalyzed by Yb(OTf)3. This methodology was highly regioselective.